Unreveling pathways of cyto and genotoxicity of AgNP in lung cells: in vitro and in vivo approach - Rosário, Fernanda de Oliveira Esteves (2020)
Silver nanoparticles (AgNPs) have been extensively used due to their antimicrobial and anti-inflammatory properties. The unique properties have been exploited in a wide range of fields, such as, medical, scientific, industrial, and in consumer products allowing the exposure through various routes including inhalation, ingestion and dermal. Although, there are many studies reporting the effects of AgNPs, is still not clear whether their toxicity is attributed to AgNPs intrinsic toxicity and/or from the released ions. Therefore, this study was sub-divided in two main hypotheses: A) small differences on AgNPs size enough to induce different toxicity profiles in lung (cell line A549) and bone cells (cell line MG-63) grown in vitro; B) the toxicity, distribution and excretion kinetics AgNPs upon instilled mice in vivo is size dependent. Therefore, in the in vitro studies, A549 and MG-63 cell lines were exposed to AgNPs with 10 nm (AgNP10) and 20 nm (AgNP20) (up to 100μg/mL), as well as ionic silver (as AgNO3). The effects on cell viability, proliferation, induced apoptosis, DNA damage and cell cycle dynamics were assessed. Also, the contribution of ionic silver (due to AgNP dissociation) on the toxicity of AgNPs was determined. Results for A549 cell line showed that for concentrations <5μg/mL, AgNP20 induced higher mortality, while AgNP10 showed higher toxicity at doses >50μg/mL. Also, for doses >50μg/mL, AgNP10 induced severe DNA damage (comet class 3-4), cell cycle arrest at G2 and induction of late-apoptosis. AgNP20 induced arrest at S phase and increase in the % sub-G1, that was not recovered after 48h. AgNP20 also induced late-apoptosis/necrosis. MG-63 results showed that AgNP20 induced cell cycle arrest at G0/G1 and decrease in cell proliferation, while AgNP10 induced severe DNA damage which lead to death by necrosis. Finally, combining both A549 and MG-63 results, we concluded that A549 are more sensitive to AgNPs and the toxicity was highly dependent on size and concentration. Additionally, a small difference in AgNP size is enough to induce a size-dependent toxicity in both cell lines, but it was not enough to influence the uptake rate by both cell lines. AgNO3 in short exposure (48h) is more toxic compared to AgNPs, however, for longer exposures AgNPs shown higher toxicity completely inhibiting cell growth. Silver toxicity, distribution and excretion of two different sizes of AgNPs (5 and 50nm) and ionic silver (AgNO3) were assessed in vivo in mice. Two experiments were performed: A) acute exposure - endpoint evaluation after 1 or 2 intratracheal instillation (IT) and recovery for 7 days; B) chronic exposure - endpoint evaluation after repeated ITs, once a week for 5 weeks. Mice were allowed to recover for 1, 2, 7, 14, 21 or 28 days after the last instillation (dpi). At the end of both studies, blood samples were collected for hematology, and the organs (brain, lung, liver, heart, spleen and kidney), urine and feces were collected to evaluate the silver concentration by ICP-MS. Lung and liver tissues were collected to GSH analysis. For the acute study only, lung tissues were collected to study the effects on the metabolic profile by NMR and for the chronic study, data was gathered to build a Physiologically based pharmacokinetic (PBPK) model. Overall, for the acute study the effects of the instilled AgNPs were dependent on size and number of instillations. The AgNP5 shared a similar inflammatory effect with AgNO3, while AgNP50, seemed to have higher influence on the innate immune system. Regarding the biodistribution results, the highest concentration of silver obtained was in the lungs, followed by blood, spleen, kidneys and liver. AgNP5 showed a faster and higher distribution to all organs but with a high rate of accumulation. The AgNP50 remained mostly in the blood with only a small fraction of silver detected in the organs, although, the small concentration of silver distributed to the organs, presented a high rate of excretion. After 2 IT of AgNPs or AgNO3, the redox state of the lungs suggested an oxidative stress response correlated to higher amounts of silver. In the liver, there was an increase in GSH for AgNP50 or AgNO3, which could be related to biliary excretion of silver as Ag-GSH complex. NMR profiling of lung tissues revealed several Ag-induced alterations in metabolites involved in different pathways, such as glycolysis and TCA cycle amino acid metabolism, phospholipid metabolism and antioxidant defense. Notably, most of the metabolic changes observed after 1 IT were reversed in animals subjected to 2 IT of AgNPs, suggesting adaptation mechanisms to recover homeostasis. Additionally, AgNO3 showed no significant alterations after 2 IT. For the chronic study, hematology results showed that AgNP5 induced major and longer lasting toxicity compared to AgNP50 and AgNO3. The redox state of both lung and liver, overall, showed an oxidative stress response which could be related to the silver exposure. The major route for excretion seems to be through the urine, especially for AgNP50 and AgNO3. Also, a high concentration of AgNP5 was also found in feces. The PBPK model was not successful predicting the real distribution of particles from 5 – 50nm. From the 7 specific tissues, the modelled data for the heart and liver were in line with the in vivo data. Overall, this study suggests that even small differences on AgNPs size are enough to induce different outcomes and effects in human cell lines. Additionally, when comparing bigger sizes differences, along with the size, the number of exposures seems to play a role in the AgNPs effects, distribution and elimination from the body.